Methane/Air Flame Control in Non-Premixed Bluff Body Burners Using Ring-Type Plasma Actuators - Fatemeh Bagherighajari; Mohammadmahdi Abdollahzadehsangroudi; José C. Páscoa (Actuators)
Enhancing the combustion efficiency and flame stability in conventional systems is essential for reducing carbon emissions and advancing sustainable energy solutions. In this context, electrohydrodynamic plasma actuators offer a promising active control method for modifying and regulating flame characteristics. This study presents a numerical investigation into the effects of a ring-type plasma actuator positioned on the co-flow air side of a non-premixed turbulent methane/air combustion system—an approach not previously reported in the literature. The ring-type plasma actuator was designed by placing electrodes along the perimeter of the small diameter wall of the air duct. The impact of the plasma actuator on the reacting flow field within the burner was analyzed, with a focus on its influence on the flow dynamics and flame structure. The results, visualized through velocity and temperature contours, as well as flow streamlines, provide insight into the actuator’s effect on flame behavior. Two operating modes of the plasma actuators were evaluated: co-flow mode, where the aerodynamic effect of the plasma actuators was directed downstream; and counter-flow mode, where the effects were directed upstream. The findings indicate that the co-flow actuation positively reduces the flame height and enhances the flame anchoring at the root, whereas counter-flow actuation slightly weakens the flame root. Numerical simulations further revealed that co-flow actuation marginally increases the energy release by approximately 0.13%, while counter-flow actuation reduces the energy release by around 7.8%.